Clinical and genetic features of rhabdoid tumors of the heart registered with the European Rhabdoid Registry (EU-RHAB) - Bartelheim, Kerstin; Sumerauer, David; Behrends, Uta; Kodetova, Daniela; Kucera, Filip; Leuschner, Ivo; Neumayer, Petra; Oyen, Florian; Rübe, Christian; Siebert, Reiner; Schneppenheim, Reinhard; Seeringer, Angela; et al. (Cancer genetics, 2014)
Rhabdoid tumors are rare but highly aggressive malignancies of infancy and early childhood with a generally unfavorable prognosis. Despite a wide variety of anatomic locations rhabdoid tumors share mutational inactivation of the SWI/SNF (SWItch/Sucrose NonFermentable) core component gene SMARCB1 (also known as INI1, hSNF5 or BAF47) in chromosome 22. As this inactivation usually results in loss of SMARCB1 expression, detectable by an antibody against the SMARCB1 protein, the accurate diagnosis of a rhabdoid tumor may be more distinctly and frequently made. Several reports on rhabdoid tumors presenting in various anatomic sites outside the kidneys and CNS are on record. We report two cases of rhabdoid tumors originating in the heart (cardiac tissue), which were entered into the European Rhabdoid Registry (EU-RHAB). The first case presented with intracardial and -cranial lesions as well as malignant ascites, while the second patient demonstrated an isolated cardiac tumor. This induced a different therapeutic approach and subsequently different clinical course (death 7 weeks after diagnosis in patient 1). Patient 2 presented with a bifocal intracardial tumor without metastases and remains in complete remission for 46 months since diagnosis following multimodal therapy. The second case demonstrates that even in a potentially futile clinical situation early and accurate diagnosis followed by prompt and intensive multimodal therapy may offer prolonged survival, potential cure and improved quality of life.
Keywords: heart; Registries; Peripheral Blood Stem Cell Transplantation; kombinovaná terapie; DNA-Binding Proteins; Infant; Humans; chromozomální proteiny, nehistonové; EU-RHAB; kojenec; DNA vazebné proteiny; registrace; Transcription Factors; nádorové supresorové proteiny; mutace; Antineoplastic Agents; SMARCB1; lidé; gen SMARCB1; Tumor Suppressor Proteins; Heart Neoplasms; Chromosomal Proteins, Non-Histone; nádory srdce; SMARCB1 Protein; Neoplasm Metastasis; metastázy nádorů; Male; intensive multimodal therapy; protinádorové látky; rhabdoidní nádor; Rhabdoid tumor; transkripční faktory; Rhabdoid Tumor; Combined Modality Therapy; Mutation; mužské pohlaví; transplantace periferních kmenových buněk